Dynamic distribution of Massilia spp. in sewage, substrate, plant rhizosphere/phyllosphere and air of constructed wetland ecosystem - Xu, Ailing; Liu, Congcong; Zhao, Shuke; Song, Zhiwen; Sun, Hui (Frontiers in Microbiology, 2023)
Massilia bacteria are widely distributed and have various ecological functions. Preliminary studies have shown that Massilia is the dominant species in constructed wetland ecosystems, but its species composition and distribution in constructed wetlands are still unclear. In this paper, the inhouse-designed primers were used to construct a 16S rDNA clone library of Massilia. The RFLP sequence analysis method was used to analyze the diversity of Massilia clone library and the composition of Massilia in sewage, substrate, plant rhizosphere, plant phyllosphere and air in a constructed wetland sewage treatment system. Redundancy analysis (RDA) and canonical correspondence analysis (CCA) were used to analyze the correlation between environmental factors and the population characteristics of Massilia in the corresponding environment. The dominant species of Massilia were analyzed for differences. The results showed that the 16S rDNA clone library in primer 5 worked well. According to the clone library diversity index analysis, the richness of Massilia varied significantly in different environments in different seasons, where the overall summer and autumn richness was higher than that in the spring and winter. The relative abundance of 5 Massilia in the constructed wetland ecosystem was greater than 1% in all samples, which were M. alkalitolerans, M. albidiflava, M. aurea, M. brevitalea and M. timonae. The seasonal variation of dominant genera was significantly correlated with environmental factors in constructed wetlands. The above results indicated that the species of Massilia were abundant and widely distributed in the constructed wetland ecosystem, and there were significant seasonal differences. In addition, the Massilia clone library of constructed wetland was constructed for the first time in this study and the valuable data of Massilia community structure were provided, which was conducive to the further study of microbial community in constructed wetland.